The ethical and legal aspects of nurse’s work related to disabled people in light of United Nations Organisation Convention and the rights of disabled people - Studnicka, Katarzyna (Nursing in the 21st Century, 2014)
THE ETHICAL AND LEGAL ASPECTS OF NURSE’S WORK RELATED TO DISABLED PEOPLE IN LIGHT OF UNITED NATIONS ORGANISATION CONVENTION AND THE RIGHTS OF DISABLED PEOPLEIntroduction. Talking about disability, its definition should be considered. Indeed, there is no one definition of this term. It is sometimes defined as a social problem, relations between people’s health and society or the environment. On 6th September 2012, the President of Poland – Bronisław Komorowski signed Convention on Disabled People Rights. Signing the above document indicates that Poland is ready for changes, which are crucial not only for the whole society, but mostly for disabled. The keynote of the convention is human freedom. Disabled people cannot be deprived of influence on his/her own life because of neither disability nor another dysfunction. Disabled person has the right to use everything, which is available for everyone. Nurses as a professional group have frequent contact with disabled people. It is important to provide them with professional help concerning living in the society thanks to knowledge of appropriate legal acts.Aim. The thesis aims to present the content and significance of United Nations Organisation Convention on Disabled People Rights. Moreover, some ethical and legal issues of nurse’s work with disabled people were included.Materials and methods. Critical analysis of available publications.Conclusions. In order to ratify the convention in Poland, some important changes need to be introduced. Introducing convention should make Polish aware that disabled have the same rights to life, culture and choices as anyone else. Through education, nurses broaden their knowledge concerning nursing of disabled people. A vital role in the fight against discrimination is played by different kinds of actions and campaigns.